Service Quality Enhancement for Young Automotive Entrepreneurs: A SERVQUAL-IPA Perspective - Layla Hafni S; Amiruddin M. Amin; Surya Safari SD; Novita Yulia Putri; Intan Purnama; Dominicus Josephus Swanto T; Yutiandri Rivai; Latifathun Kasanah (Penerbit Goodwood, 2026)
Purpose: This study evaluates the service quality of the 2024 Entrepreneurial Skills Education Program in Motorcycle Automotive Engineering using the integrated Service Quality (SERVQUAL) and Importance–Performance Analysis (IPA) approaches.Research Methodology: A quantitative descriptive approach was employed involving 40 young automotive entrepreneurs in Riau Province. Data were collected using a SERVQUAL-based questionnaire and analyzed through SERVQUAL gap analysis and IPA.Results: The SERVQUAL analysis showed negative gap scores across all service quality dimensions, indicating that participants' expectations exceeded perceived performance. Responsiveness recorded the largest gap (?3.400), followed by empathy (?1.675) and assurance (?1.175). The IPA results identified workshop cleanliness, workshop equipment, and service equipment reliability as priority areas for improvement, while clear communication and fair service should be maintained. Conclusions: The integration of SERVQUAL and IPA effectively identifies service quality gaps and improvement priorities, providing practical guidance for enhancing entrepreneurial training quality in the automotive sector.Limitations: The study was limited to 40 participants from a single training program in Riau Province, which may limit the generalizability of the findings.Contributions: This study extends the application of the SERVQUAL–IPA framework to vocational entrepreneurship training and provides practical recommendations for training institutions and policymakers to improve service quality.